2019
DOI: 10.3390/polym11121911
|View full text |Cite
|
Sign up to set email alerts
|

Shortening Stabilization Time Using Pressurized Air Flow in Manufacturing Mesophase Pitch-Based Carbon Fiber

Abstract: Oxidation–stabilization using pressurized air flows of 0.5 and 1.0 MPa could successfully shorten the total stabilization time to less than 60 min for manufacturing mesophase pitch-based carbon fibers without deteriorating mechanical performance. Notably, the carbonized fiber heat-treated at 1000 °C for 30 min, which was oxidative–stabilized at 260 °C without soaking time with a heating rate of 2.0 °C/min using 100 mL/min of pressurized air flow of 0.5 MPa (total stabilization time: 55 min), showed excellent t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 38 publications
0
9
1
Order By: Relevance
“…The morphology and dispersion degree of 50% NP‐PAN carbon nanofibers as shown in Figure 10a are obviously improved in comparison with that of preoxidized sample at ambient pressure (Figure 9a), which indicates that pressurization can accelerate the oxidative stabilization of composite nanofibers and thus shorten the oxidation time. This feasible pressure of 0.08 MPa is lower than that pressure (0.1–1.0 MPa) reported in Reference 39. Although the NP‐PAN composite nanofibers with a higher content (e.g., 80% and 110%) are not completely preoxidized at the same temperature for a short duration (3 h) as shown in Figure 10b,c, the oxidation time can be greatly shortened compared with those of at ambient‐pressure preoxidation presented in Figure 9 (12–24 h).…”
Section: Resultscontrasting
confidence: 57%
“…The morphology and dispersion degree of 50% NP‐PAN carbon nanofibers as shown in Figure 10a are obviously improved in comparison with that of preoxidized sample at ambient pressure (Figure 9a), which indicates that pressurization can accelerate the oxidative stabilization of composite nanofibers and thus shorten the oxidation time. This feasible pressure of 0.08 MPa is lower than that pressure (0.1–1.0 MPa) reported in Reference 39. Although the NP‐PAN composite nanofibers with a higher content (e.g., 80% and 110%) are not completely preoxidized at the same temperature for a short duration (3 h) as shown in Figure 10b,c, the oxidation time can be greatly shortened compared with those of at ambient‐pressure preoxidation presented in Figure 9 (12–24 h).…”
Section: Resultscontrasting
confidence: 57%
“…This could potentially increase mechanical properties and eliminate the formation of an under‐oxidized fiber core as indicated by other work with atmospheric pressure. [ 12 ]…”
Section: Resultsmentioning
confidence: 99%
“…This could potentially increase mechanical properties and eliminate the formation of an under-oxidized fiber core as indicated by other work with atmospheric pressure. [12] Table 1 presents the results of the fitting parameters to the EDS oxygen profiles, the oxygen weight at the center (ox c ) and edge (ox edge ), the average oxygen weight content from EDS, the average oxidation weight from the TGA experiments, and the percent difference between these oxidation percentages. The difference between the average oxygen percentage from TGA and EDS are compared.…”
Section: Oxidationmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhang et al studied the oxidative stabilization mechanism of CTP by free‐radical induced method, which concluded that the oxidation reaction was synergistic promoted by tremendous free radicals generated from thermolabile covalent bonds of 2,3‐dimethyl‐2,3‐diphenylbutane and reaction of pitch molecules with oxygen 13 . The oxidative stabilization time of manufacturing mesophase pitch‐based carbon fiber was successfully shortened to less than 60 min by using pressurized air flow, revealing that the higher oxygen diffusivities decreased activation energy for the oxidative stabilization and contributed to a more homogeneous oxygen distribution across transverse section of pitch fiber 20 . Furthermore, some methods, such as modifiers (Br 2 , I 2 , and S), oxidant types (H 2 O 2 , HNO 3 , and H 2 SO 4 ), and irradiation treatment (ultraviolet, plasma, and electron beam), had been performed to improve oxidative stabilization efficiency of pitch fiber 21–27 .…”
Section: Introductionmentioning
confidence: 99%